DIAGNOSTIC TOOLS FOR ASSESSING THE QUALITY OF VOCATIONAL TRAINING FOR SPECIALISTS IN ECONOMIC COLLEGES - Nahlyi, Dmytro (Professional Pedagogics, 2025)
Relevance assessing the quality of vocational training for specialists in economic colleges requires the development of effective diagnostic tools. Aim: to substantiate the necessity of developing effective diagnostic tools that will contribute to improving the quality of education and ensure the training of highly qualified specialists capable of meeting the demands of the modern labor market. Methods: this study applies a comprehensive approach encompassing literature analysis, empirical research, expert evaluation, modeling, and comparative analysis. These methods are employed to develop diagnostic tools for assessing the quality of vocational training for specialists in economic colleges. Results: a model of the methodological system for assessing the quality of vocational training for specialists in economic colleges is presented. This model features a clear structure, including target, content, instrumental, organizational-methodological, diagnostic, and results-reflective blocks. The main functions of this quality assessment model are defined, and the specific characteristics of the methodological system for assessing the quality of vocational training for specialists in economic colleges are explored. Conclusions: the developed methodological system is a comprehensive organizational and technological construct rooted in a hierarchical combination of interconnected components. These components include goals, objectives, educational content, stages, methods, forms, diagnostic tools, criteria, indicators, and assessment results. The successful implementation of this methodological system is achieved through the effective utilization of technologies for assessing the quality of specialist training in colleges.